2003
DOI: 10.1038/sj.bjc.6601204
|View full text |Cite
|
Sign up to set email alerts
|

Coexisting high-grade glandular and squamous cervical lesions and human papillomavirus infections

Abstract: The frequency of high-risk human papillomavirus (hr-HPV) genotypes in patients with adenocarcinoma in situ (ACIS) with coexisting cervical intraepithelial neoplasia (CIN), ACIS without coexisting CIN, and high-grade CIN (CIN II/III) was studied, in order to gain more insight into the relation between hr-HPV infections and the development of coexisting squamous and glandular lesions. The SPF 10 LiPA PCR was used to detect simultaneously 25 different HPV genotypes in biopsies obtained from 90 patients with CIN I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
29
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 24 publications
(48 reference statements)
6
29
0
Order By: Relevance
“…Alternatively, the difference in ACIS with and without a squamous dysplasia may reflect a decline over time in the level of detail of histopathological reporting. In this study, 57% of ACIS lesions had a concurrent squamous dysplasia, a proportion according with other studies (Colgan and Lickrish, 1990;Anciaux et al, 1997;Casper et al, 1997;Bekkers et al, 2003). The decrease in ACIS incidence was mostly seen in the 15 -29 and 45 -59 years age groups, the former outside the ages of 30 -60 years in the screening programme in the Netherlands.…”
Section: Discussionsupporting
confidence: 83%
“…Alternatively, the difference in ACIS with and without a squamous dysplasia may reflect a decline over time in the level of detail of histopathological reporting. In this study, 57% of ACIS lesions had a concurrent squamous dysplasia, a proportion according with other studies (Colgan and Lickrish, 1990;Anciaux et al, 1997;Casper et al, 1997;Bekkers et al, 2003). The decrease in ACIS incidence was mostly seen in the 15 -29 and 45 -59 years age groups, the former outside the ages of 30 -60 years in the screening programme in the Netherlands.…”
Section: Discussionsupporting
confidence: 83%
“…For references [15,17], mean age was estimated from reported age distributions using the midpoint for each age category. Reference [29] did not report mean age, however this data was reported in a related publication [52]. …”
Section: Figmentioning
confidence: 99%
“…The frequency of hrHPV genotypes (16,18,31,33,35,39,45,51,52,56,58,59,66, and 68) differs for CIN3 patients with and without AIS [8]. In this study, it was shown that there was no significant difference in the frequency of HPV-16 or HPV-45 between CIN3 patients with or without AIS.…”
Section: Introductionmentioning
confidence: 48%
“…However, the frequency of HPV-18 was significantly higher, and the frequency of hrHPV genotypes other than HPV-16, HPV-18, and HPV-45 was lower in cervical intraepithelial neoplasia lesions coexisting with AIS than in solitary cervical intraepithelial neoplasia lesions. This suggests that CIN3s, coexisting with highgrade glandular lesions, are etiologically different from squamous lesions without coexisting glandular lesions [8]. In cervical carcinogenesis, HPV is thought to inactivate the G1 pathway by inhibiting p53 and pRb proteins by E6 and E7 proteins [9,10].…”
Section: Introductionmentioning
confidence: 99%